Strategi Gerakan Dakwah Muhammadiyah - Muhammad Luthfi Alhidayat Syahrir; Muhammad Alif Mandar; Dahlan Lama Bawa (CV. ITTC INDONESIA, 2026)
This article examines the da‘wah strategy of Muhammadiyah as a model of Islamic preaching oriented toward doctrinal purification and social transformation. As a modern Islamic organization, Muhammadiyah develops da‘wah not merely as a normative-theological activity, but also as a concrete social movement implemented across various sectors of society. This study aims to analyze the theological and ideological foundations of Muhammadiyah’s da‘wah, its strategic approaches, implementation in education, social, economic, and media sectors, as well as the challenges faced in the contemporary era. The research employs a qualitative approach using a library research method by reviewing relevant scholarly literature. The findings indicate that Muhammadiyah’s da‘wah is grounded in the Qur’an and Sunnah, framed by the principles of purification (tajrid) and renewal (tajdid), and carried out through cultural, structural, and action-based (bil-hal) approaches. Despite challenges posed by globalization, technological advancement, and socio-cultural change, Muhammadiyah demonstrates strong potential to sustain an adaptive, inclusive, and progressive Islamic da‘wah.